Temporal changes in haematocrit following artemisinin-based combination treatments of uncomplicated falciparum malaria in children. Issue 1 (December 2015) - Sowunmi, Akintunde; Akano, Kazeem; Ayede, Adejumoke; Ntadom, Godwin; Fatunmbi, Bayo; Aderoyeje, Temitope; Adewoye, Elsie
Abstract Background Artemisinin-based combination treatments (ACTs) or intravenous artesunate are used in over 100 countries for uncomplicated or severe falciparum malaria. Although intravenous artesunate may cause delayed haemolytic anaemia, there is little evaluation of the temporal changes in haematocrit following ACTs. Methods Clinical and parasitological parameters were measured before and following treatment of uncomplicated falciparum malaria in children with artesunate-amodiaquine (AA) or artemether-lumefantrine (AL) over 6-weeks. Changes in haematocrit were characterized in individual patients based on a haematocrit <30 % or ≥30 % before and following treatment. Kinetics of the deficit in haematocrit from <30 % until attainment of ≥30 % were estimated by a non-compartment model. Results In 248 of 1180 children eligible for evaluation, common temporal patterns were: no change or increase in haematocrit from ≥ 30 % [50 % of patients], haematocrit >30 % at presentation declining to <30 % within 2 weeks (early monophasic fall) [19 % of patients], and haematocrit <30 % at presentation increasing to ≥ 30 % [23 % of patients]. Haematocrit >30 % at presentation declining to <30 %, 3–5 weeks later (late monophasic fall) occurred in 7 children (3 %). Fall in haematocrit ≥5 units following treatment occurred in 57 children [23 %] between 14 and 28 days after treatment began. Baseline parasitaemia and proportion with > 100, 000μL-1 asexual forms were significantly higher in children with ≥5 units compared to <5 units fall in haematocrit 21 or 28 days after treatment began. Irrespective of pattern, declines in haematocrit deficit from <30 % were mono-exponential, with similar half-times for AA- and AL-treated children (1.32 d versus 1.14 d). Anaemia half-time correlated significantly positively with anaemia recovery time in the same patients (r = 0.55, P < 0.0001). Bland-Altman analysis of 9 or 10 multiples of anaemia half-time and anaemia recovery times showed narrow limit of agreement with insignificant biases (P = 0.19 or 0.63, respectively). Conclusions In uncomplicated falciparum malaria, increases or falls in haematocrit are common following ACTs. Falls in haematocrit ≥ 5 units are common and may or may not result in early or late anaemia. In children who recovered from acute falciparum malaria-associated anaemia following ACTs, decline in haematocrit deficit is mono-exponential. Trials registration Pan African Clinical Trial RegistryPACTR201508001188143, 3 July 2015;PACTR201508001191898, 7 July 2015http://www.pactr.org .